NOTES ON THE 13TH MEETING OF THE COORDINATION AND METHODOLOGY COMMISSION ON FORENSIC SCIENCE OF THE COUNCIL OF MINISTERS OF JUSTICE OF THE EURASIAN ECONOMIC COMMUNITY - N. Govorina (Теория и практика судебной экспертизы, 2014)
.